The Concentration and Sublimation of Time as Memory in Louise Glück's Poetry (Papers in Arts and Humanities, 2022)
The preoccupation with the mythical time of humanity, and of each individual’s life constitutes one of the most powerful poetic tools in Louise Glück’s poems. From evoking the foundational times of the Garden of Eden, or the ‘immutable’ hard nut represented by Greek mythology, the poet concentrates whatever may suggest an evolution in time in those initial ‘moments.’ Her reading of the history of the human soul seems to suggest that everything stopped with the first page, or the first words. This study argues that Glück’s use of memory or anamnesis (αʼ νάμνησις) as the only path to understanding humanity is present in many of her poems; such vision is more than just mythological literary reference, it supports the idea that childhood memories, relationships, poetic quests, and spiritual journeys are nothing but an expression of such vision. The poems chosen for this paper are not in a chronological order in terms of their time of publication. Nevertheless, we have tried to put them in a chronological order in terms of how they illustrate the idea of time as a sequence of memories accompanying the poet throughout her literary career. We will also argue that this way of treating memory and time, together with the references to mythology, to a decayed Garden, to the precarious condition of man, and to the role of the poet can support the idea that Louise Glück has a Romantic–Classical profile.
Keywords: mythical time; memory; poetic function; Greek mythology; foundational stories